Lack of Effects of Extended Sessions of Transcranial Direct Current Stimulation (tDCS) Over Dorsolateral Prefrontal Cortex on Craving and Relapses in Crack-Cocaine Users - Klauss, Jaisa; Anders, Quézia Silva; Felippe, Luna Vasconcelos; Ferreira, Leonardo Villaverde Buback; Cruz, Mateus Amorim; Nitsche, Michael Andreas; Nakamura-Palacios, Ester Miyuki (Frontiers in Pharmacology, 2018)
Background: Non-invasive brain stimulation such as transcranial direct current stimulation (tDCS) has been investigated as additional therapeutic tool for drug use disorder. In a previous study, we showed that five sessions of tDCS applied bilaterally over the dorsolateral prefrontal cortex (dlPFC) reduced craving to the use of crack-cocaine in inpatients from a specialized clinic. In the present study, we examine if an extended number of sessions of the same intervention would reduce craving even further and affect also relapses to crack-cocaine use. Methods: A randomized, double-blind, sham-controlled, clinical trial with parallel arms was conducted (https://clinicaltrials.gov/ct2/show/NCT02091167). Crack-cocaine patients from two private and one public clinics for treatment of drug use disorder were randomly allocated to two groups: real tDCS (5 x 7 cm2, 2 mA, for 20 minutes, cathodal over the left dlPFC and anodal over the right dlPFC, n = 19) and sham-tDCS (n = 16). Real or sham-tDCS was applied once a day, every other day, in a total of 10 sessions. Craving was monitored by a 5-item obsessive compulsive drinking scale once a week (one time before, three times during and once after brain stimulation) over about five weeks and relapse was monitored after their discharge from clinics for up to 60 days. Results: Craving scores progressively decreased over five measurements in both sham- and real tDCS groups. Corrected Hedges’ within-group (initial and final) effect sizes of craving scores were of 0.77 for the sham-tDCS and of 0.97 for the real tDCS group. The between-groups effect size was of 0.34, in favor of the real tDCS group over sham-tDCS group. Relapse rates were high and quite similar between groups in the 30- and 60-days follow-up after discharge from the hospital. Conclusions: Extended repetitive bilateral tDCS over the dlPFC had no add-on effects over regular treatment when considering craving and relapses to the crack-cocaine use in a sample of crack-cocaine patients with severe use disorder. Different tDCS montages targeting other cortical regions and perhaps additional extension of sessions need to be investigated to reach more efficiency in managing craving and relapses to crack-cocaine use.